Identifying the socio-economic impacts of the 2019-2020 refugee occupation and COVID-19 related restrictions on immigrant-owned businesses in the urban informal sector of Greenmarket Square, Cape Town - Madurai, Micheala (Department of Sociology, 2023)
The socio-economic impacts of the 2019-2020 Greenmarket Square refugee occupation and the COVID-19 pandemic related restrictions are the central focus of this study. More specifically, the impacts of both - the occupation and the pandemic related restrictions - on African immigrant-owned businesses in the informal craft market of Greenmarket Square (GMS). This research explored this impact using a qualitative approach. Participants were selected using a non-probability purposive sampling approach to include both men and women immigrants from Africa who traded in the GMS craft market from a stall. Interviews were conducted both face-to-face and via telephone and supplemented by direct non-participant observation. The main findings included that the refugee occupation and associated noise, smells and crime repelled the primary customers – tourists. Discrimination between the immigrant stall owners and refugees and vice versa was also rife at this time. A few months later, COVID-19 arrived in South Africa and the related travel restrictions, lockdowns and trading limitations negatively impacted the potential for economic recovery of the entrepreneurs. Participants of this research shared insight about their economic hardships, which they faced with minimal external support. Participants needed to initiate survival tactics to generate any income. The knock-on impact included the suspension of remittances for families in their countries of origin. Although these businesses have started operating again, there are still challenges. These informal craft businesses will take a long time to get back to previous levels of income generation; however, stall-owners remain optimistic. Understanding how the African immigrant stall-owners navigated these challenges provides insight into immigrant livelihoods and survival strategies, as well as indicating their determination and capacity to strive against the odds.